Esophageal Stenting With Sutures: Time to Redefine Our Standards?. Issue 6 (July 2015) - Sharaiha, Reem Z.; Kumta, Nikhil A.; Doukides, Theodore P.; Eguia, Vasco; Gonda, Tamas A.; Widmer, Jessica L.; Turner, Brian G.; Poneros, John M.; Gaidhane, Monica; Kahaleh, Michel; Sethi, Amrita
Abstract : Background and Study Aims: Migration is the most common complication of the fully covered metallic self-expanding esophageal stent (FCSEMS). Recent studies have demonstrated migration rates between 30% and 60%. The aim of this study was to determine the effect of fixation of the FCSEMS by endoscopic suturing on migration rate. Patient and Methods: Patients who underwent stent placement for esophageal strictures and leaks over the last year were captured and reviewed retrospectively. Group A, cases, were patients who underwent suture placement and group B, controls, were patients who had stents without sutures. Basic demographics, indications, and adverse events (AEs) were collected. Kaplan-Meier analysis and Cox regression modeling were conducted to determine estimates and predictors of stent migration in patients with and without suture placement. Results: Thirty-seven patients (18 males, 48.65%), mean age 57.2 years (±16.3 y), were treated with esophageal FCSEMS. A total of 17 patients received sutures (group A) and 20 patients received stents without sutures (group B). Stent migration was noted in a total of 13 of the 37 patients (35%) [2 (11%) in group A and 11 (55%) in group B]. Using Kaplan-Meier analysis and log-rank analysis, fixation of the stent with suturing reduced the risk of migration ( P =0.04). There were no AEs directly related to suture placement. Conclusions: Anchoring of the upper flare of the FCSEMS with endoscopic sutures is technically feasible and significantly reduces stent migration rate when compared with no suturing, and is a safe procedure with very low AEs rates.